2015
DOI: 10.1158/1535-7163.mct-14-0743
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Pharmacological Evaluation of Letrozole as a Novel Treatment for Gliomas

Abstract: We present data that letrozole, an extensively used aromatase inhibitor in the treatment of estrogen receptor-positive breast tumors in postmenopausal women, may be potentially used in the treatment of glioblastomas. First, we measured the in vitro cytotoxicity of letrozole and aromatase (CYP19A1) expression and activity in human LN229, T98G, U373MG, U251MG, and U87MG, and rat C6 glioma cell lines. Estrogen receptor (ER)positive MCF-7 and ER-negative MDA-MB-231 cells served as controls. Cytotoxicity was determ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…However, Dave et al described that letrozole an AI significantly reduced tumor volume (75%) in a GBM rat model, eight days after the treatment onset. These authors report a marked reduction in aromatase expression [25]. In this work, we also observe a significant reduction in aromatase expression in tumor tissue treated with anastrozole.…”
Section: Discussionsupporting
confidence: 83%
“…However, Dave et al described that letrozole an AI significantly reduced tumor volume (75%) in a GBM rat model, eight days after the treatment onset. These authors report a marked reduction in aromatase expression [25]. In this work, we also observe a significant reduction in aromatase expression in tumor tissue treated with anastrozole.…”
Section: Discussionsupporting
confidence: 83%
“…Due to the estrogenic action of BPA, this review primarily focuses on in vivo assessments of carcinogenesis in the male and female reproductive tracts as well as other proposed estrogen target tissues (a summary of studies is presented in Table 1). However, we do not exclude any non-reproductive tissues from this analysis as the list of estrogen target tissues continues to expand [33-35]. Similar to the NTP and the International Agency on Research on Cancer (IARC), we evaluate the strength of the evidence to gauge the carcinogenicity of BPA and not the potency of its carcinogenic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are not only concordant with those reported in conventional glioma cell lines by Dave et al . [41] but also extend these previous findings to a more clinically relevant experimental models such as glioma stem cells by integrating cell type-specific targeting approach based on the utilization of surface biomarkers expressed in GBM cells.…”
Section: Discussionmentioning
confidence: 65%
“…[41] investigated the efficacy of the aromatase inhibitor, Letrozole, on GBM cell growth in vitro and in vivo exclusively in the conventional human glioma cell lines and the rat glioma C6 cells. Several studies have shown that treatment response in established glioma cells differs greatly to that noted in patient-derived primary cultures [42, 43].…”
Section: Discussionmentioning
confidence: 99%